On the statistical estimation of the initial probability distribution based on the observations of dynamics at the end of an interval - Tkeshelashvili, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We consider a problem of the estimation of density of a random value that is an initial value of some dynamics. The dynamics is determined by differential equation whose solution is observable at the end of an interval. This problem is called a problem of the estimation with the use of indirect observations. By using a method of transformation of a measure along an integral curve in combination with kernel estimates, we present a procedure of the estimation of density.